Long-term methamphetamine self-administration increases mesolimbic mitochondrial oxygen consumption and decreases striatal glutathione. (1st April 2023) - Dominguez-Lopez, Sergio; Ahn, Bumsoo; Sataranatarajan, Kavithalakshmi; Ranjit, Rojina; Premkumar, Pavithra; Van Remmen, Holly; Beckstead, Michael J.
Abstract: Neurotoxic regimens of methamphetamine (METH) are known to increase reactive oxygen species (ROS), affect redox homeostasis, and lead to damage in dopamine neurons. Functional changes induced by long-term METH self-administration on mitochondrial respiratory metabolism and redox homeostasis are less known. To fill this gap, we implanted a jugular catheter into adult male mice and trained them to nose poke for METH infusions. After several weeks of METH exposure, we collected samples of the ventral striatum (vST) and the ventral midbrain (vMB). We used HPLC to determine the levels of the ROS scavenger glutathione in its reduced (GSH) and oxidized forms. Then, we used high-resolution respirometry to determine the oxygen consumption rate (OCR) of mitochondrial complexes. Finally, using in vivo electrophysiology, we assessed changes in dopamine neuron firing activity in the VTA. METH self-administration produced a decrease of the GSH pool in vST, correlating with lifetime METH intake. We observed increased mitochondrial respiration across the two mesolimbic regions. METH self-administration decreases firing rate and burst activity but increases the number of spontaneously active dopamine neurons per track. We conclude that METH self-administration progressively decreased the antioxidant pool in sites of higher dopamine release and produced an increase in mitochondrial metabolism in the mesolimbic areas, probably derived from the increased number of dopamine neurons actively firing. However, dopamine neuron firing activity is decreased by METH self-administration, reflecting a new basal level of dopamine neurotransmission. Highlights: We exposed mice to intravenous methamphetamine (METH) self-administration for 30–100 days. We detected a depletion of the antioxidant molecule glutathione (GSH) in the ventral striatum. In parallel, we observed an increase in mesolimbic mitochondrial complex respiration. Spontaneously active dopamine neurons with low firing rates and low burst activity increased in the ventral tegmental area. We identify mesolimbic GSH deficiency and increased mitochondrial respiration as conditions accompanying chronic METH use.